Study on the Clinical Significance of ACE2 and Its Age-Related Expression - Gu J; Yin J; Zhang M; Li J; Wu Y; Chen J; Miao H (Dove Medical Press, 2021)
Jie Gu,1,* JiangWen Yin,1,* MengJie Zhang,1,* JinHui Li,1 YeMing Wu,2 Jun Chen,1 HongJun Miao1 1Department of Emergency/Critical care Medicine, Children's Hospital of Nanjing Medical University, Nanjing, Jiangsu Province, 210008, People's Republic of China; 2Center of Interventional Radiology and Vascular Surgery, Department of Radiology, Zhongda Hospital, Medical School of Southeast University, Nanjing, Jiangsu Province, 210009, People's Republic of China*These authors contributed equally to this workCorrespondence: Jun Chen; HongJun MiaoDepartment of Emergency/Critical care Medicine, Children's Hospital of Nanjing Medical University, No. 72 GuangZhou Road, Nanjing, Jiangsu Province, 210008, People's Republic of ChinaTel +86 13813951884; +86 18951769627Fax +86 02583117488Email chenjundr850@21cn.com; drmiaohj16@88.comBackground: ACE2 plays a particular role in the changes in multiple organ functions. However, whether ACE2 expression differs at different ages and whether it plays a role in infection-related organ dysfunction remains unclear.Methods: Female and male C57BL/6 mice in four different age groups were included in this study. Immunohistochemical and Western blot analyses were performed to evaluate ACE2 expression characteristics in lung tissues. At the same time, we detected the changes of ACE2 in human blood of different ages and evaluated its clinical significance in sepsis-associated organ dysfunction (SAOD).Results: This study indicated that ACE2 is expressed differently in mouse lung tissues at four different ages (P < 0.05). The peak expression distribution of ACE2 in lung tissues was in the newborn and middle-aged cohorts (P < 0.05). Infants younger than one year had a significantly higher concentration of ACE2 in serum and enhanced susceptibility compared with other ages (P < 0.05). Serum APTT, D-dimer, LDH, and PCT, as well as ACE2 in sepsis and SAOD groups, were statistically significant (P < 0.05) and were related to an increased risk of SAOD. There was a positive correlation between ACE2 and D-dimer (P < 0.05).Conclusion: The levels of ACE2 expression varied in different age groups. It tends to be higher in infants and young children. This result suggests that young children are more susceptible to infection. Moreover, a cutoff value for the ACE2 level > 1551.15 pg/mL and D-dimer > 984.5 U/L should be considered a warning sign of infection-associated organ dysfunction and guide the clinician in evaluating the patient's multiple organ function.Keywords: ACE2, SAOD, infection, organ dysfunction, clinical significance